Arthroscopic Bankart versus open Latarjet as a primary operative treatment for traumatic anteroinferior instability in young males: a randomised controlled trial with 2-year follow-up - Kukkonen, Juha; Elamo, Sami; Flinkkilä, Tapio; Paloneva, Juha; Mäntysaari, Miia; Joukainen, Antti; Lehtinen, Janne; Lepola, Vesa; Holstila, Milja; Kauko, Tommi; Aarimaa, Ville; Ryösä, Anssi; et al. (British journal of sports medicine, 2022)
ObjectivesTo compare the success rates of arthroscopic Bankart and open Latarjet procedure in the treatment of traumatic shoulder instability in young males.DesignMulticentre randomised controlled trial.SettingOrthopaedic departments in eight public hospitals in Finland.Participants122 young males, mean age 21 years (range 16–25 years) with traumatic shoulder anteroinferior instability were randomised.InterventionsArthroscopic Bankart (group B) or open Latarjet (group L) procedure.Main outcome measuresThe primary outcome measure was the reported recurrence of instability, that is, dislocation at 2-year follow-up. The secondary outcome measures included clinical apprehension, sports activity level, the Western Ontario Shoulder Instability Index, the pain Visual Analogue Scale, the Oxford Shoulder Instability Score, the Constant Score and the Subjective Shoulder Value scores and the progression of osteoarthritic changes in plain films and MRI.Results91 patients were available for analyses at 2-year follow-up (drop-out rate 25%). There were 10 (21%) patients with redislocations in group B and 1 (2%) in group L, p=0.006. One (9%) patient in group B and five (56%) patients in group L returned to their previous top level of competitive sports (p=0.004) at follow-up. There was no statistically significant between group differences in any of the other secondary outcome measures.ConclusionsArthroscopic Bankart operation carries a significant risk for short-term postoperative redislocations compared with open Latarjet operation, in the treatment of traumatic anteroinferior instability in young males. Patients should be counselled accordingly before deciding the surgical treatment.Trial registration numberNCT01998048.